A proposed conceptual framework of supply chain operations reference (SCOR) model in Indonesian industries: a literature review - Antonius Setyadi; Erry Rimawan; Ivan Kristanto; Puspita Eka Rohmah (Universitas Mercu Buana, 2022)
This article uses the approach of a literature review study sourced from previous research and relevant to this research, namely the Supply Chain Operations Reference model. The phenomenon is that previous studies have not reviewed the Supply Chain Operations Reference (SCOR) model as an interesting thing to study in collaboration with other methods in a structured way. This study aims to give a proposed framework of the SCOR model as a reference for detailed information related to the SCOR model in Indonesia's retail, manufacturing, and service industries. The results of the paper are the year of publication for the 50 articles reviewed consists of 2018-2021 for the country of Indonesia. The research object consists of 3 objects, namely the retail, manufacturing, and service industries. Most supply chain performance levels in Indonesia are in a good category. Most of the research variables majority of the five variables often used in the SCOR model: plan, source, make, deliver, and return. The performance attribute priority that needs to be improved is the reliability attribute. The method used by previous research is 17 methods. This method can be used as an illustration to see how the SCOR model can collaborate with other methods. The paper's conclusion is the research proposed framework regarding the application of the SCOR model that can be collaborated with other methods.